Chemical and isotopic architecture of the belemnite rostrum. (15th June 2015) - Ullmann, C.V.; Frei, R.; Korte, C.; Hesselbo, S.P.
Abstract: Macrofossil calcite is of great importance for quantitative reconstructions of palaeoenvironment and palaeoseasonality. The calcite rostra of belemnites, Jurassic to Cretaceous marine invertebrates, are especially suited for such investigations, because they are comparatively large and are structured by growth bands. Despite their use in chemostratigraphic and palaeoenvironmental studies, much of the internal variability of geochemical signatures in rostra is poorly understood. Here, multiple profiles through a belemnite rostrum of Passaloteuthis bisulcata (∼183 Myr old) were analyzed for δ 13 C and δ 18 O values as well as Mg/Ca, Sr/Ca and Mn/Ca ratios. Geochemical signatures of the central 1–2 mm of the profiles indicate diagenetic cementation along the apical zone, for which original porosity of up to 40% can be inferred. The overall δ 13 C and δ 18 O values of the other, well preserved parts of the belemnite fluctuate by >1 per mil, but are nearly uniform within single growth bands. In contrast, Sr/Ca and Mg/Ca in the well-preserved parts show growth-rate and crystal-shape related variability. Close to the central apical zone, strongly bent calcite crystals are enriched in Mg (up to 70%) and Sr (up to 50%). Through the remainder of the rostrum, higher calcite precipitation rate can account for Mg depletion of ∼15% and Sr enrichment of ∼15% with respect to co-genetic calcite precipitated at a slower rate. No indication for temperature control on Mg/Ca or Sr/Ca is detected in the investigated specimen. Overall, the new findings indicate that δ 13 C and δ 18 O analyses of belemnite rostra produce consistent results regardless of the sampling area within the rostrum, and that growth rate effects on element incorporation are minor with respect to the control exerted by secular changes in seawater composition through time. Additionally, the central part of the rostrum, where strong calcite crystal bending is observed, should be avoided for sampling when studying elemental composition of the calcite for palaeoenvironmental reconstructions.